Zimbabwe : Technical Assistance Report-Basel III Implementation. (IMF Staff Country Reports; Country Report ;, 2022)
As a follow-up to the 2019 FSSR, a remote TA mission supported the RBZ with the implementation of Basel III liquidity standards. The mission reviewed the RBZ drafts of the LCR and NSFR frameworks, discussed identified material gaps with the BSD management and relevant supervisors, and provided many recommendations on enhancing the drafts of liquidity regulations, monitoring tools, reporting templates, and disclosure. Further actions for implementing Basel III liquidity standards were agreed with the RBZ.